Złotousty kaznodzieja bohaterem dramatów z początku XX wieku - Mieszek, Małgorzata (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
The article described dramas of Jan Bełcikowski, Roman Borelowski and Władysław Banduski. They were written to grace the celebration of the 300th anniversary of Piotr Skarga’s death in 1912. These texts were performed in Cracow and Lvov. Skarga was created as a romantic visionary and the prophet. These creations corresponded to a lofty tonality of jubilee celebrations. The article brings issues of the construction of characters. A problem of the adaptation of Skarga’s texts is also taken into account. Authors intercepted especially excerpts of Kazania sejmowe. The article takes under consideration description of the historical background. Dramas which are subject of the article met with unfavourable opinions of historians of literature. They accused dramas, that aren’t growing beyond the level of “occasional works”, which are marked by a schematism and a naivety. However, these charges weren’t confirmed with any analysis. That is why, the article tries to answer the question of what caused the negative evaluation of these literary productions and whether indeed these dramas are deserving of so explicitly negative evaluation.